2D self-assembly of o-OPE foldamers for chiroptical barcoding. Issue 7 (6th February 2023) - López-Sicilia, Irene; Ortuño, Ana M.; Reine, Pablo; Otero, Dario; Martín-Romero, María T.; Camacho, Luis; Álvarez de Cienfuegos, Luis; Orte, Angel; Giner-Casares, Juan J.; Miguel, Delia; Cuerva, Juan M.
Abstract : 2D films of enantiopure stapled o -OPEs have been used to develop a CPL-barcoding system free of photoselection artifacts. The use of both enantiomers makes the system easier and safer to read. Abstract : We report on the preparation and characterization of two dimensional (2D) films of ( S, S, P )-1 and ( R, R, M )-1 ortho -oligophenylene ethylene ( o -OPE) enantiomers presenting high values of circularly polarized luminescence (CPL). The amphiphilic character of these two molecules allows a precise 2D self-assembly at the air/water interface and an efficient transfer onto a glass solid support. The morphological and chiroptical characterization of the solid supports after the transfer of 1, 8, 16 and 32 Langmuir films of ( S, S, P )-1 and ( R, R, M )-1 has been carried out. The strong chiroptical values of these monomers allow reliable ECD measurements to be obtained after a single transfer, with ECD values increasing as the number of transferred films increases. The semi-liquid behavior of the monomers on the solid substrate allows CPL measurements free of photoselection artifacts that show values similar to those obtained in solution and independent of monomer concentration. All these properties have allowed us to develop the first simple organic molecule (SOM)-based chiroptical barcoding presenting positive and negative regions as a proof of concept.